482 Triple Therapy Versus Dual Antiplatelet Therapy for Dolichoectatic Vertebrobasilar Fusiform Aneurysms Treated With Flow Diverters: The Last Frontier?. (April 2023) - Siddiqui, Adnan Hussain; Monteiro, Andre; Hanel, Ricardo; Kan, Peter; Mohanty, Alina; Cortez, Gustavo; Rabinovich, Margarita; Matouk, Charles Christian; Sujijantarat, Nanthiya; Romero, Charles Edward; Stone, Jeremy Guy; Ebersole, Koji C.; et al.
Abstract : INTRODUCTION: Dolichoectatic vertebrobasilar fusiform aneurysms (DVBFAs) have poor natural history when left untreated and high morbimortality when treated with microsurgery. Flow diversion (FD) with dual-antiplatelet therapy (DAPT) is feasible but carries a high risk of perforator occlusion and progression of brainstem compression. Seeking better hopes for these patients, experts across the US started using triple-therapy (DAPT plus oral anticoagulation) after FD treatment in attempt to improve their clinical outcomes. The rationale was to preserve perforator patency while vessel remodeling occurs. The current study is the result of this multicenter effort. METHODS: Retrospective data collection from 8 US centers. Only DVBFAs treated with flow-diversion and either triple-therapy or DAPT alone were included. Patient and aneurysms' characteristics, and clinical and angiographic outcomes were compared. RESULTS: The groups (DAPT, n = 13 vs Triple-therapy, n = 14) were similar in age, sex, clinical presentation, baseline disability, aneurysm characteristics, median number of flow-diverters, and adjunctive coiling. Radial access use was significantly higher in the triple-therapy group (71.4% vs. 15.3%, P = 0.006). Acute ischemic stroke rate was lower in the triple-therapy group (7.1% vs. 30.8%, P = 0.167). Overall rate of modified Rankin Scale score decline due to either ischemic stroke or worsening of brainstem compression was significantly lower in the triple-therapy group (7.1% vs. 69.2%, P = 0.001). Overall rate of hemorrhagic complications was numerically higher in the triple-therapy group (28.6% vs. 7.7%, P = 0.162). The rate of moderate-to-severe disability at last follow-up was significantly lower in the triple-therapy group (21.4% vs. 76.9%, P = 0.007). I. CONCLUSIONS: Patients with DVBFAs treated with FD and triple-therapy had less ischemic strokes, less symptom progression, and overall better outcomes at last follow-up than similar patients and aneurysms managed with DAPT alone.